INPP4B inhibits glioma cell proliferation and immune escape via inhibition of the PI3K/AKT signaling pathway - Sun, Xiaoming; Chen, Yani; Tao, Xiaoyang; Zhang, Wenzi; Wang, Xinyu; Wang, Xianhui; Ruan, Zhihua; Chen, Zhuo (Frontiers in Oncology, 2022)
INPP4B (Inositol polyphosphate 4-phosphatase type II) has been regarded as a suppressor of several human tumors, but its biological function, expression, and clinical significance in glioma tissues and cell lines are unclear. Notably, whether INPP4B participates in immune escape of glioma deserves urgent attention. Here, we confirmed that INPP4B expression is often downregulated in low- and high-grade human glioma tissues, in tissues from an orthotopic mouse model of brain glioma and in glioma cells. We found that INPP4B overexpression restrained the proliferation, migration, apoptosis resistance, PD-L1 expression, and T cell suppression by glioma cells, whereas INPP4B silencing had the opposite effects. Moreover, we showed that INPP4B inhibited glioma cell proliferation, migration, and PD-L1 expression by downregulating PI3K/AKT signaling. Collectively, these data support that INPP4B may inhibit glioma progression, and particularly, glioma’s immune escape. Thus, INPP4B may constitute a valuable target for glioma treatment.